PENGKAYAAN β-KAROTEN PADA COKELAT BATANG DENGAN PENAMBAHAN Spirulina platensis - Himawasesa P. Negara; Iwan Y. B. Lelana; Nurfitri Ekantari (Universitas Gadjah Mada, 2014)
The aim of this research was to determined the level of acceptance of the panelists as well as β-carotene content of the chocolate bars which is enriched with Spirulina platensis. This research used Completely Randomized Design. Spirulina platensis was added at various concentrations 0, 5, 10, 15% (w/w). Each treatment was repeated 3 times. The results showed that chocolate bar was added 5% S. platensis is the most preferred treatment by panelists, with characteristics as follows: no ﬁshy odor, no bitter taste and its texture when in the mouth like slightly sandy. The chemical content of this product were 1,63% moisture, 3,83% ash , 9,22% protein, 56,24% fat, and 29,08% carbohydrate. Besides that, its had 70,33 μg /g of β-carotene which is equivalent to 11,72 RE /g. Consuming 30 g chocolate bar enriched S.platensis 5 % ( w/w ) per day could provide for 60-70 % of the vitamin A, served an energy of 197,81 kcal intake and 351,6 RE provitamin A or supplied 9,65% of the energy needs and fulﬁ ll 50% -70% of vitamin A base on recommended daily intake.